HBV DNA integration: molecular mechanisms and clinical implications - Tu, Thomas; Urban, Stephan (Viruses, 2017)
Chronic infection with the Hepatitis B Virus (HBV) is a major cause of liver-related morbidity and mortality. One peculiar observation in cells infected with HBV (or with closely‑related animal hepadnaviruses) is the presence of viral DNA integration in the host cell genome, despite this form being a replicative dead-end for the virus. The frequent finding of somatic integration of viral DNA suggests an evolutionary benefit for the virus; however, the mechanism of integration, its functions, and the clinical implications remain unknown. Here we review the current body of knowledge of HBV DNA integration, with particular focus on the molecular mechanisms and its clinical implications (including the possible consequences of replication-independent antigen expression and its possible role in hepatocellular carcinoma). HBV DNA integration is likely to influence HBV replication, persistence, and pathogenesis, and so deserves greater attention in future studies.
Gesehen am 12.09.2018